Stratified haploid identification system through the R1-nj kernel and reduced seedling vigor in tropical maize germplasm - ARNAT THAWARORIT; ABIL DERMAIL; KAMOL LERTRAT; SOMPONG CHANKAEW; KHUNDEJ SURIHARN (Society for Indonesian Biodiversity, 2023)
Abstract. Thawarorit A, Dermail A, Lertrat K, Chankaew S, Suriharn K. 2023. Stratified haploid identification system through the R1-nj kernel and reduced seedling vigor in tropical maize germplasm. Biodiversitas 24: 4262-4268. Haploid identification through the R1-nj marker is commonly applied in in-vivo doubled haploid technology in maize, although misclassification issues often occur. We explored the innate properties of maternal haploids at the seedling stage to verify true haploids and to reduce false positives. There are many questions about whether reduced seedling vigor is effective for haploid verification in tropical maize backgrounds. This study aimed to evaluate the haploid induction rate of Stock6-derived F3 population inducers and to investigate the effectiveness of reduced seedling vigor at the V2/V3stage as an alternative marker to verify putative haploids. Field trials and haploid induction were conducted in the rainy season of 2021 and the dry season of 2021/22 in Khon Kaen, Thailand. Two tropical source germplasm: P789 and S7328, were included as donor females. Haploids were identified through the R1-nj marker and reduced seedling vigor. Significant reduction of haploid frequency up to 2.5% on average between the two identification methods, indicating that a considerable number of false positives could be found using reduced seedling vigor. Inducer population K11 was promising since it performed a stable ability to produce haploids over donors and seasons and had a low misclassification rate. Further breeding strategies and haploid selection schemes are discussed.